Predilection of Grammarians: An analytical study - Al-Sharari, Khaled Saleh (Journal of Humanities & Social Sciences, 2022)
"Istehsan" or "Predilection” is considered as one of the debatable criteria in the Arabic grammar which lie in the heart of the grammatical thought in Arabic. Based on an analytical approach, this research aims to identify the Arabic grammarians’ application of predilection norms in different grammatical categories of Arabic, and to demonstrate the reasons behind using it to make inferences, as well as the grammarians’ controversy concerning these grammatical issues. The research consists of an introduction, three sections and a conclusion. In the introduction, the relationship between two fields humanities – the Islamic jurisprudence and the Arabic grammar – is examined, since the scholars of Islamic jurisprudence were the first to introduce the term “predilection” to Arabic studies. The first section discusses in detail the use of predilection in the Islamic Jurisprudence. The second section investigates how and for which purpose the term is used by the Arabic grammarians. The third section shows its applications by Arabic grammarians, how it could be used to make inferences, and the grammarians’ different views on whether to take it as a reliable standard or not.